INTERRELATION OF RHOMBICITY AND OCCURRENCE OF INTERNAL CRACKS AT CONTINUOUS CASTING OF SORTED SLUG - Ju. A. Samojlovich; V. I. Timoshpolski; S. M. Kabishov; R. B. Vajs (Литьë и металлургия)
Analysis of deformations and stresses in cross section of sorted uninterruptedly-casted slugs at their solidification and cooling within limits of crystallizer with the aim of determination of possibilities for occurrence of internal cracks of diagonal type is carried out on basis of mathematical modeling, the peculiarities of the slug skin cooling at its shrinkage and separation from crystallizer wall are revealed.